A comparative study on the effect of fixation for guinea pigs eyeballs among three different fixation solution - Hui-Xin Song (Guoji Yanke Zazhi, 2018)
AIM: To compare the effect of fixation and select the optimal fixation solution and condition for PAS staining of guinea pig eyes among three different fixation solution: 4% paraformaldehyde solution, 4% glutaraldehyde solution and Davidson solution. METHODS: Totally 30 healthy guinea pigs were divided into 6 groups: Group I-II were fixed in 4% paraformaldehyde solution and 4% glutaraldehyde solution for 24h, respectively; Group III-V were fixed in Davidson solution for 3, 6 and 24h, respectively; and Group VI were fixed in Davidson solution for 3h and then transferred into 10% neutral formaldehyde solution for 48h. All groups were sectioned by routine section method and undergone PAS staining, and then observed by light microscope. RESULTS: It was found that the group which was fixed by Davidson solution for 3h, remained the most complete structure for PAS staining(Group III). While the effect of fixation for the group which was transferred into 10% neutral formaldehyde solution for preserving for 48h after fixing in Davidson solution for 3h was also acceptable for PAS staining(Group VI). The retinal cells remained clear and in order for both groups which was mentioned above. CONCLUSION: The best fixation condition for PAS staining for eyes of guinea pigs is fixation in Davidson solution for 3h among these fixation conditions, while it is also suitable to transfer the eyes into neutral formaldehyde solution after fixing in Davidson solution for 3h for preserving for long periods, which is not severely reduced the effect of fixation for PAS staining.